Enhanced biosynthesis of withanolides by elicitation and precursor feeding in cell suspension culture of Withania somnifera (L.) Dunal in shake-flask culture and bioreactor. - Ganeshan Sivanandhan (Public Library of Science (PLoS), 2014)
The present study investigated the biosynthesis of major and minor withanolides of Withania somnifera in cell suspension culture using shake-flask culture and bioreactor by exploiting elicitation and precursor feeding strategies. Elicitors like cadmium chloride, aluminium chloride and chitosan, precursors such as cholesterol, mevalonic acid and squalene were examined. Maximum total withanolides detected [withanolide A (7606.75 mg), withanolide B (4826.05 mg), withaferin A (3732.81 mg), withanone (6538.65 mg), 12 deoxy withanstramonolide (3176.63 mg), withanoside IV (2623.21 mg) and withanoside V (2861.18 mg)] were achieved in the combined treatment of chitosan (100 mg/l) and squalene (6 mM) along with 1 mg/l picloram, 0.5 mg/l KN, 200 mg/l L-glutamine and 5% sucrose in culture at 4 h and 48 h exposure times respectively on 28th day of culture in bioreactor. We obtained higher concentrations of total withanolides in shake-flask culture (2.13-fold) as well as bioreactor (1.66-fold) when compared to control treatments. This optimized protocol can be utilized for commercial level production of withanolides from suspension culture using industrial bioreactors in a short culture period.